Prarancangan Pabrik Amonium Nitrat dengan Proses UHDE Kapasitas 165.000 Ton/Tahun - Utami, Endah Bekti; , Ir. Haryanto Abdul Rofiq, M.S; , Rois Fatoni S.T., M.Sc., Ph.D (2017)
The design of ammonium nitrate plant with UHDE process capacity of 165.000 ton/year aims to meet the needs of ammonium nitrate in Indonesia. Ammonia and nitric acid are reacted in a bubble reactor, using the uhde process on the grounds that this process is a very popular alternative because it has the lowest investment cost. The mole ratio of nitric acid and ammonia is 1: 1.01. The reaction takes place at a temperature of 140⁰C with a pressure of 3 atm, which is exothermic. Then the product will be concentrated by evaporating water using evaporator type Long Tube Vertical. Utility needs in each year in the form of cooling water needs of 29,587.76 kg / hour, steam provider of 2,427.06 kg / hour. Electricity as much as 196.27 kW and compressed air as much as 634.70 m3 / hour. The plant is planned to operate for 330 days. Economic analysis shows the amount of fixed capital of Rp 451.154.629.304,27 and working capital of Rp 245,648,679,757,02. While profit before tax of Rp 115,039,968,977.31 and profit after tax of Rp 80,527,978,284,12. Percent Return on Investment (ROI) before tax of 25.50% and after tax of 17.85%. Pay Out Time (POT) before tax 2.82 years and after tax of 3.59 years. Break Event Point (BEP) of 55.2% and Shut Down Point (SDP) of 34.39%. From the feasibility analysis data can be concluded that this factory is profitable and feasible to be established.